A Work Motivation Strengthening Program to Enhance Employee Performance in Financial Services Organizations - AR Hidayat; Gary Leonard Hendrik; Andi Rinda Oktariani; Andi Reski Nurhikmah (PT. Global Research Collaboration, 2025)
This community engagement program aims to strengthen work motivation as a strategic effort to improve employee performance within financial services organizations. The primary challenge faced by management involved declining morale, reduced commitment, and decreasing service quality, which collectively impacted overall productivity. To address these issues, the program implemented a series of motivation-enhancing activities, including training sessions, group discussions, role-play simulations, and coaching, utilizing a participatory approach. Employees were actively involved in identifying core problems, reflecting on work behaviors, and developing action plans and collective commitments. The results indicate a significant improvement in motivation, discipline, and job satisfaction. Based on pre-test and post-test evaluations, work motivation increased by 22.4%, accompanied by measurable improvements in both individual and team performance. The program effectively contributed to strengthening a productive and service-oriented work culture, demonstrating that participatory interventions can serve as an effective strategy to enhance employee performance in the financial services sector.